Mutter und Sohn im Briefwechsel : 1917 - 1946 - Scholem, Betty 1866-1946 (Eine Veröffentlichung des Leo-Baeck-Instituts, 1989)
Betty Scholem/Gershom Scholem: "Mutter und Sohn im Briefwechsel 1917-1946". C. H. Beck Verlag, München 1989. 579 S., 13 Abb., geb., 58,- DM